Acute Kidney Injury and Hypothyroidism in a Patient with CKD - Preeti Chandra; Abdolreza Haririan; Cinthia Drachenberg (MDPI AG, 2022)
Acute kidney injury (AKI) in the setting of hypothyroidism has been documented in the literature. However, hypothyroidism is not generally considered a cause during investigation of an acute kidney injury. Most of the cases described have been reported in setting of rhabdomyolysis, while fewer cases describe AKI occurring in the absence of rhabdomyolysis. Only rarely have case reports been supplemented by renal biopsy findings to ensure other etiologies of acute kidney injury were ruled out, and none of these reports have documented changes in the kidney that could be associated with the hypothyroid state. We report a case of AKI in chronic kidney disease in the absence of rhabdomyolysis, occurring during severe hypothyroidism, that resolved completely after achievement of a euthyroid state. In addition, we provide renal biopsy findings likely associated with the hypothyroid state. We propose that evaluation of the thyroid function should be considered in any patient during evaluation of an acute kidney injury.